Study of Contamination Control in The Pharmaceutical Industry: Ethylene Glycol and Diethylene Glycol - Anugrah, Resmilia; Nurhalisa Kairupan, Daning; Liyana Putri, Fadhilah; Ulfa, Munira; Pratama, Fenryco (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Contamination cases in health products are on the rise, mainly due to ethylene glycol and diethylene glycol contaminants, which contribute to the high number of child deaths. Contamination caused by toxic compounds should be controlled and minimized to ensure public safety and security. Therefore, contamination control needs further review. This paper aims to discuss HACCP and GMP procedures for controlling and minimizing contaminants in the pharmaceutical industry, as well as policies and coordination between actors to prevent the recurrence of cases of ethylene glycol and diethylene glycol contamination. The research used the literature study method, with hazing's publication or perish as a search tool. The results of this paper show that in the application of HACCP, there are several critical control points, namely the manufacture of drugs, the removal of materials, screening of raw materials, dry mixing, mixing, and packaging. GMP implements controls on sanitation and hygiene, equipment, self-inspection and supplier approval audits, personnel, training, personal hygiene, and locations and buildings. In order to prevent the recurrence of contamination cases, it is necessary to apply policies related to suppliers of raw materials, raw materials, and the application of GMP. Coordination between actors at the country and company scales is necessary to prevent the recurrence of ethylene glycol and diethylene glycol contamination cases.